A THIRST FOR RARITY? AN INTERESTING CASE OF HYPOPITUITARISM. Issue 12 (15th November 2016) - Edwards, Marc; Johnston, JA
Abstract : A previously healthy 69-year-old short statured woman presented with a 4-month history of increased thirst, polyuria, nausea, vomiting, 2-stone weight loss and nocturnal visual hallucinations. Neurological examination was normal, however she had difficulty standing due to postural hypotension with a supine blood pressure of 98/64 mm Hg. Investigations revealed hypopituitarism with secondary hypoadrenalism (baseline cortisol of 45 nmol/l) and hypothyroidism. Neuroimaging showed leptomeningeal enhancement and an infundibular mass lesion, which on biopsy demonstrated a benign non-Langerhan cell histiocytic proliferation with a likely diagnosis of Rosai-Dorfman disease. Extensive systemic investigation for extranodal and extra-CNS disease has been unremarkable. The patient has made a complete symptomatic recovery with pituitary replacement therapy of thyroxine and hydrocortisone and is monitored with serial neuroimaging and visual field testing. Rosai Dorfman disease is a macrophage-related disorder consisting of histiocytic accumulation and proliferation. It is often systemic, involving lymph nodes but can have extranodal involvement; common extranodal sites are the skin, respiratory tract, bones and in the CNS. The aetiology is currently unclear but isn't believed to be neoplastic. Accumulation of histiocytes can however cause compression on important structures and in this case it's likely that pituitary stalk compression from the infundibular mass caused this patient's constellation of symptoms.